Transnational Migration and Work in Asia - Hewison, Kevin; Young, Ken (Routledge/City University of Hong Kong Southeast Asia Series, 2006)
Focusing on the issues associated with migrating for work both in and from the Asian region, this book sheds light on the debate over migration and trafficking. With contributions from an international team of well-known scholars, the book sets labour migration firmly within the context of globalization, providing a focused, contemporary discussion of what is undoubtedly a major twenty-first century concern. Transnational Migration and Work in Asia analyzes workers motivations and rationalities, highlighting the similarities of migration experiences throughout Asia. Presenting in-depth case studies of the real-life experiences and problems faced by migrant workers, the book discusses migrants' relations with the state and their vulnerability to exploitation, as well as the major policy issues now facing governments, employers, NGOs and international agencies.